Non-invasive Brain Stimulation for Central Neuropathic Pain - Yang, Qi-Hao; Zhang, Yong-Hui; Du, Shu-Hao; Wang, Yu-Chen; Fang, Yu; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
The research and clinical application of the noninvasive brain stimulation (NIBS) technique in the treatment of neuropathic pain (NP) are increasing. In this review article, we outline the effectiveness and limitations of the NIBS approach in treating common central neuropathic pain (CNP). This paper summarizes the research progress of NIBS in the treatment of different CNPs and describes the effects and mechanisms of these methods on different CNPs. rTMS analgesic research has been relatively mature and applied to a variety of CNP treatments. But the optimal stimulation targets, stimulation intensity, and stimulation time of tDCS for each type of CNP are still difficult to identify. The analgesic mechanism of rTMS is similar to that of tDCS, both of which change cortical excitability and synaptic plasticity, regulate the release of related neurotransmitters and affect the structural and functional connections of brain regions associated with pain processing and regulation. Some deficiencies are found in current NIBS relevant studies, such as small sample size, difficulty to avoid placebo effect, and insufficient research on analgesia mechanism. Future research should gradually carry out large-scale, multicenter studies to test the stability and reliability of the analgesic effects of NIBS.